Adaptive capacity and climate change: the role of community opinion leaders. Issue 4 (2nd April 2016) - Keys, Noni; Thomsen, Dana C.; Smith, Timothy F.
Abstract : The contribution of the informal community sector to the development of collective response strategies to socioecological change is not well researched. In this article, we examine the role of community opinion leaders in developing and mobilising stocks of adaptive capacity. In so doing, we reveal a largely unexplored mechanism for building on latent social capital and associated networks that have the potential to transcend local-scale efforts – an enduring question in climate change adaptation and other cross-scalar sustainability issues. Participants drawn from diverse spheres of community activity in the Sunshine Coast, Australia, were interviewed about their strategies for influencing their community objectives and the degree to which they have engaged with responding to climate change. The results show community opinion leaders to be politically engaged through rich bridging connections with other community organisations, and vertically with policy-makers at local, state, national and international levels. Despite this latent potential, the majority of community opinion leaders interviewed were not strategically engaged with responding to climate change. This finding suggests that more work is needed to connect networks knowledgeable about projected climate change impacts with local networks of community opinion leaders. Attention to the type of community-based strategies considered effective and appropriate by community opinion leaders and their organisations also suggests avenues for policy-makers to facilitate community engagement in responding to climate change across sectors likely to be affected by its impacts. Opportunities to extend understanding of adaptive capacity within the community sector through further research are also suggested.